INTEGRATION OF WEB 2.0 TOOLS IN LIBRARY SERVICES: A STUDY OF INDIAN UNIVERSITY LIBRARIES - ., Sumeeta; Kumar Sharma, Sanjay (Journal of Advanced Research in Library and Information Science; Vol 12 No 3 (2025): Journal of Advanced Research in Library and Information Science, 2025)
Web 2.0 technology has altered Indian academic libraries, especially university libraries. Blogs, wikis, RSS feeds, social media, and more have made libraries more accessible and increased communication, collaboration, and knowledge sharing. Web 2.0 encourages user participation, real-time changes, and two-way communication between libraries and their users, as opposed to the static, one-way communication that was common in earlier library systems. This study looks at how university libraries in India are using Web 2.0 tools to bring their services up to date, increase user engagement, and close the digital divide. This article explores the consequences on students, teachers, and researchers as well as the level of integration and the challenges that have been experienced. To survive in this age of information overload and changing user expectations, Indian universities must implement Web 2.0 strategies into their library programs if they want to attract and retain students. The reason for this is that these establishments are completely embracing the digital revolution.